Case Control Analysis of Fetal Congenital Heart Defects as a Risk Factor for Preeclampsia [10N]. (May 2018) - Bears, Breanne; Browne, Kathleen; Turan, Shifa; Turan, Mehmet
Abstract : INTRODUCTION: Fetal congenital heart defects (fCHD) may indicate an angiogenic imbalance that predisposes mothers to pre-eclampsia (PE.) It is unclear if this is due to other maternal risk factors of PE or from CHD itself. We sought to determine whether fCHD is an independent risk factor for maternal PE. METHODS: This was a case control study of singleton births delivered at the University of Maryland Medical Center from 2007 to 2016. Fetuses with CHD diagnosed by a fetal echocardiography were identified. Known chromosomal anomalies were excluded. The primary exposures of interest were known maternal risk factors for PE. Controls were matched 1 to 3 by history of PE, diabetes mellitus (DM, ) and chronic hypertension (CHTN). Risk of PE was analyzed in fCHD vs. non-fCHD pregnancies. Data was analyzed using Chi-squared. RESULTS: 251 fCHD cases met inclusion criteria. These were matched with 753 controls. PE occurred in 15 (6%) deliveries with fCHD and 44 (5.8%) matched controls. Early PE (<34 wks) occurred in 4 (1.6%) fCHD and 10 (1.3%) control pregnancies. Late PE (>34 wks) occurred in 11 (4.4%) fCHD and 34 (4.5%) controls. The presence of fCHD was not associated with PE (OR: 0.98; CI 0.53-1.79; p=0.94). When PE was separated into early and late, CHD was not associated with either early (OR=0.83; CI 0.26-2.67; p=0.75) or late PE (OR: 1.03; CI 0.51-2.07; p=0.93). CONCLUSION: Fetal CHD was not an independent risk factor for PE, early PE, or late PE. Further monitoring does not appear warranted in women with antenatal diagnosis of fCHD.